(untitled) (Research, Society and Development, 2021)
The present study aimed to investigate the postural balance of elderly people with and without Type 2 Diabetes Mellitus (DM2) and to verify the associated clinical characteristics. It is an observational, analytical and cross-sectional study; 233 elderly people (60 years or older) were evaluated, 147 with a diagnosis of DM2 (G1) and 86 without DM2 (G2). Postural balance was assessed using the Mini - The Balance Evaluation Systems Test (MiniBESTest). The associations between the total scores of G1 and G2 were verified using the Mann-Whitney tests and the Chi-square test, α = 0.05. After inferential analysis, significance was observed between variables in groups G1 and G2: BMI (p = 0.048), number of medications (p = 0.001), motor TUGt (p = 0.015), FPP (p <0.001), WHODAS ( p = 0.011), EDG (p = 0.001), presence of changes in the feet (p <0.001), calluses (p <0.001), joint changes (p <0.001), dermatological changes (p <0.001), vibratory sensitivity (p <0.001), skin-protective sensitivity (p <0.001), orthostatic hypotension (p = 0.003) and fear of falls (p = 0.002). The MiniBesTest average was 22.15 ± 4.64 points for the group with DM2 and 21.94 ± 4.89 points for the group without DM2. Significance was also observed in the Mini BESTest domains: anticipatory adjustments (p = 0.001) and postural responses (p = 0.042) in the elderly with and without DM2. G1 elderly people have greater impairment of postural balance when associated with the presence of depressive symptoms, decreased mobility, the presence of comorbidities, polypharmacy, changes in the feet and fear of falling.